Dasar Pertimbangan Hakim dalam Menjatuhkan Pidana terhadap Pelaku Tindak Pidana Persetubuhan Anak atas Kesepakatan Bersama dalam Perspektif Keadilan - Frans A. Kabnani; Karolus Kopong Medan; Rudepel Petrus Leo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to examine the ethical and moral considerations of judges in imposing verdicts against perpetrators of the crime of child intercourse, as reflected in Decision Number 147/Pid.Sus/2023/PN Kpg. This case is complex because the perpetrator and the victim are both still classified as minors and sexual relations occurred on the basis of consensual, but are still qualified as criminal acts based on positive Indonesian law. The main focus of this study is how judges balance protection for victims with justice for perpetrators who are also still in their childhood, as well as the extent to which the principle of restorative justice is applied in the verdict. This study uses an empirical juridical method with a qualitative approach, which relies on document studies, interviews, and analysis of court decisions. The theories used in the analysis are the theories of restorative justice, substantive justice, and child protection in the criminal justice system. The results of the study showed that the judge imposed criminal punishment on the perpetrator even though there were elements of agreement and the status of the perpetrator who was still a child. The judge's main consideration is the legal protection of children as absolute victims. However, judges do not optimally consider the approach to coaching and restorative justice as regulated in the juvenile justice system. The victim's family's refusal to mediate was also a factor that strengthened the criminal verdict. On the other hand, there is an inequality in the application of the principle of fairness, because the perpetrator is not fully positioned as a child who also needs protection and coaching.